2014
DOI: 10.1167/iovs.14-13997
|View full text |Cite
|
Sign up to set email alerts
|

Examination of VLC-PUFA–Deficient Photoreceptor Terminals

Abstract: Very long chain PUFAs affect rod function by contributing to synaptic vesicle size, which may alter the dynamics of synaptic transmission, ultimately resulting in a loss of neuronal connectivity and death of rod photoreceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 38 publications
2
63
1
Order By: Relevance
“…ERG was performed as described (Bennett et al, 2014) in order to analyze the various stages of the retinal response to light. These studies revealed that the outer segment-mediated a-wave was significantly reduced in the KO mice compared to WT mice.…”
Section: Loss Of Vlc-pufa Results In Rod-mediated Functional Deficitsmentioning
confidence: 99%
See 4 more Smart Citations
“…ERG was performed as described (Bennett et al, 2014) in order to analyze the various stages of the retinal response to light. These studies revealed that the outer segment-mediated a-wave was significantly reduced in the KO mice compared to WT mice.…”
Section: Loss Of Vlc-pufa Results In Rod-mediated Functional Deficitsmentioning
confidence: 99%
“…Recordings were performed under standard conditions as described previously (Bennett et al, 2014;Van Hook and Thoreson, 2013). There was no significant difference in I Ca between WT and KO mice, indicating that loss of presynaptic I Ca are not responsible for any decreases in synaptic transmission in KO mice (Figs.…”
Section: Loss Of Vlc-pufa Results In Rod-mediated Functional Deficitsmentioning
confidence: 99%
See 3 more Smart Citations